Sediment core description of GeoB24367-1 (MUC25) recovered during R/V Sonne expedition SO278 at Sartori MV in the Calabrian Arc, Mediterranean Sea - Mechthild Doll; Nele Behrendt; Agathe Eijsink; Gerhard Bohrmann (PANGAEA, 2024)
Sediment core GeoB24367-1 (MUC25) was collected during R/V Sonne expedition SO278 using a multi corer. The position is close to the Sartori Mud Volcano located in the Calabrian accretionary prism (Mediterranean Sea). To capture the sedimentary structure, the multi core was longitudinally split and the archive halve was photographed using a camera at a 300-dpi resolution. To investigate lithological changes in more detail, a macroscopic core description is prepared. The core description provides information regarding core length, exact position, water depth, number of core sections, core image, color, lithology, sedimentary structures and a descriptive text. Sediment color was determined qualitatively using Munsell soil color charts.